Identifying the Underserved: An Analysis of a Free Eye Clinic’s Demographics - Imran Nizamuddin; Ahsan Hussain; Ravali Gummi; Birju Solanki (Journal of Student-Run Clinics, 2018)
Background: The Kansas City Free Eye Clinic (KCFEC) is a student-run free clinic dedicated to providing comprehensive eye exams and treatment to the underserved populations of the Kansas City metropolitan area. Since the clinic’s inception, volunteers have observed firsthand the great need for eye care and the impact of poor vision on health, employment, and education. As a result, services provided continue to expand, with the goal of incorporating novel communities into the treatment network. The purpose of this study was to review patient demographics in order to identify possible barriers to care and shortcomings in outreach efforts. Methods: Medical records for patients seen at the KCFEC between December 2014 and July 2016 were reviewed for demographics including age, gender, ethnicity, housing status, and insurance status. Results: Analysis of 334 patient records indicated that the average patient at KCFEC was a 45-year-old African American male who is uninsured and homeless. Certain groups, including females, individuals below 40 years of age, individuals above 65 years of age, and patients belonging to other minority groups, were not as prevalent at KCFEC. Conclusions: Further investigation of potential barriers to care disproportionately experienced by these groups will be the next step in efforts to increase the clinic’s impact. With the aid of periodic retrospective review of patient demographics, KCFEC aims to be a source of accessible and quality healthcare to a diverse group of patients in Kansas City.